2000
DOI: 10.1034/j.1600-0404.2000.101003202.x
|View full text |Cite
|
Sign up to set email alerts
|

Auditory P300 event related potential in minor ischemic stroke

Abstract: Brain infarction delays the P300 ERP and temporarily distorts its age-related physiology. The increase of the P300 latency seems to be associated with the post-stroke depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 0 publications
1
9
1
1
Order By: Relevance
“…However, recent ERP studies [48][49] showed that the influence of alcohol quantity in university students was restricted to a decreased in neuronal processing speed. Several degenerative brain diseases are known to cause abnormalities restricted to the latency of ERP components, such as brain infarction, which slightly delays the P3 latency without affecting its amplitude or scalp distribution [50]. Anatomically, this variability in P3 latency is mainly related to white matter connectivity, also known to be altered by alcohol consumption [51].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent ERP studies [48][49] showed that the influence of alcohol quantity in university students was restricted to a decreased in neuronal processing speed. Several degenerative brain diseases are known to cause abnormalities restricted to the latency of ERP components, such as brain infarction, which slightly delays the P3 latency without affecting its amplitude or scalp distribution [50]. Anatomically, this variability in P3 latency is mainly related to white matter connectivity, also known to be altered by alcohol consumption [51].…”
Section: Discussionmentioning
confidence: 99%
“…This increase might be due to the microdegenerative changes of arterial type and the atrophy of right hippocampus, however it cannot be verified if these slight changes can explain such extremely high latencies. P300 latency may increase slightly in minor ischemic stroke and this increase is associated with post-stroke depression [12], which was not diagnosed in our patient. No increased P300 latency has been observed in patients with vascular cognitive impairment [13].…”
Section: Discussionmentioning
confidence: 92%
“…P300 abnormalities are particularly connected to certain cognitive deficits such as defective short term memory, perceptual processing speed, and decreased alertness and attention in patients with dementia and in older age population. The decreased P300 latency is believed to reflect maturation as well as the speed of the cognitive processes [8].…”
Section: Discussionmentioning
confidence: 99%
“…Considerable interest exists in the utilization objective and easily administered measures of cognitive dysfunction that can be used to follow patients and also to demonstrate the clinical benefits of various therapeutic interventions [5]. Event related potential (ERP) records electrical manifestations of the brain's perception and response to external stimuli [6] P300, is one of the most commonly recorded and studied type of ERP [7] and is an electrical signal produced by the brain during the performance of various cognitive tasks [8]. P300 recording has been used to evaluate brain mechanisms underlying cognition and to characterize information processing in normal subjects as well as patients with neurological disorders [9].…”
Section: Introductionmentioning
confidence: 99%